PENGUATAN CIVIC LITERACY DALAM PEMBELAJARAN DEMOKRASI DAN PEMILU DAN IMPLIKAISNYA TERHADAP CIVIC ATITUDE MAHASISWA - Erna Yuliadari; Rusnaini Rusnaini; Yudi Ariana (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2018)
The level of literacy of the students in the subjects of democracy and elections are still low. Civic literacy became a prosecution along with the advances and advances in technology and the current globalization. This research aims to map out the civic literacy students, knowing the strategy of strengthening civic literacy in learning democracy and elections as well as to know the implications of the strengthening of civic literacy against civic atitude students. The methods used in this research in the form of qualitative descriptive. The data source used is the quisioner, interviews, observation, documents and studies supported by Focus Group Discussion (FGD). Location research in the civic education study programs Faculty of teacher training and the education. Research results showed civic literacy students relating to problems – problems or issues – issues in democracy and elections are lacking it is seen when a student performs an analysis of the outstanding issues and develop in the public good of the mass media both print and social media, students can not provide an analysis of those issues because the student is not at all know those issue Keywords: civic literacy, democracy and elections, civic atitude